Diagnostic ultrasound assessment of deep fascia sliding mobility in vivo: A scoping review – Part 2: Femoral and crural fasciae. (July 2021) - Soares, Hélio Rafael; Pinheiro, Ana Rita; Crasto, Carlos; Barbosa, Pedro; Dias, Nuno; de Carvalho, Paulo
Abstract: Background: Failure of fascial sliding may occur in cases of excessive or inappropriate use, trauma, or surgery, resulting in local inflammation, pain, sensitization, and potential dysfunction. Therefore, the mechanical properties of fascial tissues, including their mobility, have been evaluated in vivo by ultrasound (US) imaging. However, this seems to be a method that is not yet properly standardized nor validated. Objectives: To identify, synthesize, and collate the critical methodological principles that have been described in the literature for US evaluation of deep fascia sliding mobility in vivo in humans. Methods: A systematic literature search was conducted on ScienceDirect, PubMed (Medline), Web of Science and B-On databases, according to the PRISMA Extension for Scoping Reviews (PRISMA-ScR) guidelines. The OCEBM LoE was used to evaluate the level of evidence of each study. Results: From a total of 104 full-text articles retrieved and assessed for eligibility, 18 papers were included that evaluate the deep fasciae of the thoracolumbar (n = 4), abdominal (n = 7), femoral (n = 4) and crural (n = 3) regions. These studies addressed issues concerning either diagnosis (n = 11) or treatment benefits (n = 7) and presented levels of evidence ranging from II to IV. Various terms were used to describe the outcome measures representing fascial sliding. Also, different procedures to induce fascial sliding, positioning of the individuals being assessed, and features of US devices were used. The US analysis methods included the comparison of start and end frames and the use of cross-correlation software techniques through automated tracking algorithms. These methods had proven to be reliable to measure sliding between TLF, TrA muscle-fascia junctions, fascia lata, and crural fascia, and the adjacent epimysial fascia. However, the papers presented heterogeneous terminologies, research questions, populations, and methodologies. This two-part paper reviews the evidence obtained for the thoracolumbar and abdominal fasciae (Part 1) and for the femoral and crural fasciae (Part 2). Conclusion: The US methods used to evaluate deep fascia sliding mobility in vivo in humans include the comparison of start and end frames and the use of cross-correlation software techniques through automated tracking algorithms. These seem reliable methods to measure sliding of some fasciae, but more studies need to be systematized to confirm their reliability for others. Moreover, specific standardized protocols are needed to assess each anatomical region as well as study if age, sex-related characteristics, body composition, or specific clinical conditions influence US results.